Estimating Demographic Parameters for Bearded Seals, Erignathus barbatus, in Alaska Using Close‐Kin Mark‐Recapture Methods - Brian D. Taras; Paul B. Conn; Mark V. Bravington; Andrzej Kilian; Aimée R. Lang; Anna Bryan; Raphaela Stimmelmayr; Lori Quakenbush (Evolutionary Applications)
ABSTRACT Reliable estimates of population abundance and demographics are essential for managing harvested species. Ice‐associated phocids, “ice seals,” are a vital resource for subsistence‐dependent coastal Native communities in western and northern Alaska, USA. In 2012, the Beringia distinct population segment of the bearded seal, Erignathus barbatus nauticus, was listed as “threatened” under the US Endangered Species Act requiring greater scrutiny for management assessments. We sought to estimate requisite population parameters from harvested seals by using close‐kin mark‐recapture (CKMR) methods, the first such application for marine mammals. Samples from 1758 bearded seals harvested by Bering, Chukchi, and Beaufort Sea communities during 1998–2020 were genotyped, genetically sexed, and aged by tooth annuli. After rigorous quality control, kin relationships were established for 1484 seals including two parent–offspring pairs (POPs) and 25 potential second‐order kin pairs. Most of the second‐order kin were half‐sibling pairs (HSPs), but four were potential grandparent‐grandchild pairs (GGPs). There were no full sibling pairs, suggesting a lack of mate fidelity. Mitochondrial DNA analysis identified 17 potential HSPs as paternally related, providing substantial evidence of persistent heterogeneity in reproductive success among adult males. The statistical CKMR model incorporates probabilities associated with POPs, HSPs, and GGPs and assumes known ages and a stable population. Our top model accommodates heterogeneity in adult male breeding success and yields an abundance estimate of ~409,000 with a coefficient of variation (CV) = 0.35, which is substantially greater than the “non‐heterogeneity” model estimate of ~232,000 (CV = 0.21), an important difference for managing a harvested species. Using CKMR methods with harvested species provides estimates of abundance with the added opportunity to acquire information about adult survival, fecundity, and breeding success that could be applied to other species of concern, marine and terrestrial.